The Representation of Monarchism and Rebellion: Power Struggles Depicted in The King (2019) Movie - Hendri Purnomo; Ana Widiyanti (Metaphor, 2024)
This study attempts to examine how the 2019 David Michod film "The King" depicts revolt and the monarchical order. The film tells the tale of Prince Hal, who succeeds his father, King Henry IV, as King Henry V. Hal had to deal with a number of difficulties as a young monarch, such as disagreements with disobedient noblemen. Qualitative approaches are the primary tool used in this study. The 2019 film "The King" serves as the primary source of data. The process of gathering data involved reading, observing, recognizing, categorizing, and choosing pertinent information. As part of the data analysis process, the data were presented, clarified, and interpreted using conflict theory. According to the findings, the film portrays the monarchical system of medieval Europe, in which the king, who holds the throne for successive generations, possesses ultimate power. The film also depicts insurrection brought on by dissatisfaction with the king's choices. In addition, the movie looks at how unrest could be sparked by instability and discontent inside the royal circle.